Not to save, but to encounter: Fitzpatrick as transnational jurisprudent. Issue 1 (March 2021) - Pahuja, Sundhya
Abstract: This essay sketches the lineaments of the relationship between international law and the jurisprudence of Peter Fitzpatrick. It argues that Fitzpatrick was a model 'transnational jurisprudent' who accepted responsibility for the ongoing conduct of lawful relations, even as he offered a thoroughgoing critique of occidental law. For the occidentally trained international lawyer, Fitzpatrick's work offers a way to take up that responsibility by reimagining international law through its historical roots as a parochial law of encounter.